Proceedings of the 2017 International Conference on Education and Technology (2017 ICEduTech) 2018
DOI: 10.2991/icedutech-17.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emotional Quotient, Academic Loyalty, and Interpersonal Communication on Lecturersr Performance of Mulawarman University Samarinda

Abstract: The objective of this research is to study of effect of emotional quotient, academic loyalty, and interpersonal communication on lecturers' performance of Mulawarman University Samarinda. The data of this research were collected through the use of questionnaire filled out by 130 lecturers chosen randomly by using random sampling technique. The data were obtained by administering questionnaire and analyzed with path analysis. The results of research showed that: (1) emotional quotient positively has significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…He explains that human communication is a process through which individuals in relationships, in groups, in organizations, and in society create, transmit, and use the information to coordinate their environment and others. This finding supports Haryaka (2018), who found that interpersonal communication had a direct positive effect on lecturer performance.…”
Section: Discussionsupporting
confidence: 88%
“…He explains that human communication is a process through which individuals in relationships, in groups, in organizations, and in society create, transmit, and use the information to coordinate their environment and others. This finding supports Haryaka (2018), who found that interpersonal communication had a direct positive effect on lecturer performance.…”
Section: Discussionsupporting
confidence: 88%
“…is one of the opportunistic (facultative) ectoparasites, which means Trichodina sp. can live without a host and can infect and cause disease in the host if conditions are favourable, such as fish stress, the host's immune system decreases, or environmental conditions that support the development of pathogens such as high organic matter content and low dissolved oxygen in water 5 . The high or low prevalence and intensity of Trichodina sp.…”
Section: Table 4 Prevalence and Intensity Of Ectoparasites In Goldfis...mentioning
confidence: 99%
“…Ectoparasites are parasites that stick (live) on the outside/surface of the host's body, such as skin, scales, and gills 4 . Ectoparasites in fish are often found on the outside/surface of the fish body, such as scales, skin, mucosa, fins, operculum, gills, eyes, and nose 5 . Prevalence is the disease frequency at a certain time in a population 6 .…”
Section: Introductionmentioning
confidence: 99%